2020
DOI: 10.1523/jneurosci.0548-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differentiation of Mouse Visual Cortical Areas Depends upon Early Binocular Experience

Abstract: The mammalian visual cortex contains multiple retinotopically defined areas that process distinct features of the visual scene.Little is known about what guides the functional differentiation of visual cortical areas during development. Recent studies in mice have revealed that visual input from the two eyes provides spatiotemporally distinct signals to primary visual cortex (V1), such that contralateral eye-dominated V1 neurons respond to higher spatial frequencies than ipsilateral eye-dominated neurons. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The values of optimal SFs at PW3 obtained by intrinsic imaging and two-photon Ca 2+ imaging in the present study are similar to those just after eye-opening previously reported via electrophysiological recordings in mice (Hoy & Niell, 2015). In addition, the optimal SF values after PW3 are similar to those reported in some previous studies on adult mice (Hoy & Niell, 2015;Durand et al 2016) but lower than in others (Salinas et al 2017(Salinas et al , 2021. This difference may be ascribed to the differences in the recording sites in the visual cortex.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The values of optimal SFs at PW3 obtained by intrinsic imaging and two-photon Ca 2+ imaging in the present study are similar to those just after eye-opening previously reported via electrophysiological recordings in mice (Hoy & Niell, 2015). In addition, the optimal SF values after PW3 are similar to those reported in some previous studies on adult mice (Hoy & Niell, 2015;Durand et al 2016) but lower than in others (Salinas et al 2017(Salinas et al , 2021. This difference may be ascribed to the differences in the recording sites in the visual cortex.…”
Section: Discussionsupporting
confidence: 89%
“…We further show that this developmental shift requires visual experience during a particular period in postnatal development. A recent study employing two-photon Ca 2+ imaging demonstrated that 2-week monocular deprivation of juvenile mice causes a decrease in optimal SFs in the adult visual cortex (Salinas et al 2021). Thus, normal visual experience seems to be required for a developmental increase in optimal SFs.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in visual response strength induced by cMD were limited to deprived eye responses, and therefore differed from the response to MD at the peak of the critical period, in which deprived eye depression is followed by an increase in the strength and selectivity of non-deprived eye responses [ 2 , 35 , 50 , 51 ]. The decrease in the strength of visual responses following cMD was observed across a range of spatial frequencies and contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of neuronal responses in mouse V1b as binocular has recently come under scrutiny [ 37 , 59 , 60 , 61 , 62 ]. Central to this debate is the role of inclusion criteria in the definition of visually-evoked GCaMP activity, as the adaptation of high-threshold inclusion criteria excludes contributions from the non-dominant eye [ 51 ]. However, in our hands, increasing the threshold for the inclusion of visually-evoked activity from the non-dominant eye did not reduce the number of neurons categorized as binocular in any experimental populations of adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Third, ocular dominance has been shown to result from the competition between neurons and neural networks to represent and process environmental and internal information 44 46 . For instance, the dominance of one eye over the other was a direct function of the amount of light stimulating the dominant eye in birds 44 .…”
Section: Implications Of Neural Competitionmentioning
confidence: 99%